The Malaysian Historical Geographical Information System (MHGIS): The Case of Chinese Temples in Johor - Hue, Guan Thye (Religions, 2023)
This is a quantitative study of Chinese temples in Johor using temple data to show the development of Chinese religion in the state. The study finds that Chinese temples in Johor are dominated by a fusion of Confucianism, Buddhism and Daoism, with only a minority of orthodox Buddhism in existence. The broad range of Buddhist and Daoist deities shows the diversity and inclusiveness of the religion. In addition, the number of newly created temples in the state is still on the rise, contradicting the perception that they, especially Daoist ones, are on the decline. The quantitative data collation and analysis of Chinese temples in Johor not only will reflect more accurately the development of religion and beliefs of the local Chinese community, but also is an attempt to construct Malaysia Historical Geographic Information System (MHGIS). We hope that in the future, we can make use of the convenience of the data humanities system to make a more macro and holistic exploration and development of the study of Chinese temples and beliefs in Malaysia.